2014
DOI: 10.1103/physrevb.90.054504
|View full text |Cite
|
Sign up to set email alerts
|

Spin supercurrent, magnetization dynamics, andφ-state in spin-textured Josephson junctions

Abstract: The prospect of combining the dissipationless nature of superconducting currents with the spin-polarization of magnetic materials is interesting with respect to exploring superconducting analogues of topics in spintronics. In order to accomplish this aim, it is pivotal to understand not only how such spin-supercurrents can be created, but also how they interact dynamically with magnetization textures. In this paper, we investigate the appearance of a spin-supercurrent and the resulting magnetization dynamics i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 73 publications
3
68
2
Order By: Relevance
“…For any coplanar magnetization distribution there exists a global SU(2) spin rotation that flips the direction of M, and the condition (3) is fulfilled. For this reason, the AJE requires a noncoplanar magnetization texture as predicted for ballistic S/F/F/F/S systems [32][33][34]. The anomalous current obtained in those works shows rapid oscillations as a function of the ferromagnetic thickness.…”
Section: Introductionmentioning
confidence: 87%
“…For any coplanar magnetization distribution there exists a global SU(2) spin rotation that flips the direction of M, and the condition (3) is fulfilled. For this reason, the AJE requires a noncoplanar magnetization texture as predicted for ballistic S/F/F/F/S systems [32][33][34]. The anomalous current obtained in those works shows rapid oscillations as a function of the ferromagnetic thickness.…”
Section: Introductionmentioning
confidence: 87%
“…30. Furthermore, the dynamics of both JJs with misaligned ferromagnetic layers and those coupled to single or multiple ferromagnetic layers have also been studied numerically 31 . It has also been shown that the presence of a single classical spin of a molecular magnet precessing under the action of a constant magnetic field coupled to a JJ may lead to generation of finite spin current whose polarization axis rotates with same frequency as the classical spin 32 .…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Such junctions have been predicted to occur in ferromagnetic Josephson junctions with spinorbit interactions [30], in Josephson junctions containing a multilevel quantum dot with spin-orbit coupling and a magnetic field [31], in Josephson junctions with spinorbit nanowires subject to magnetic fields [32], in multiterminal quantum-dot Josephson junctions subject to frustration between 0 and π states [33], and in complex ferromagnetic Josephson junctions [34][35][36][37]. In the latter type of setup, the occurrence of a ϕ junction has recently been confirmed experimentally [38].…”
Section: Introductionmentioning
confidence: 99%